2020
DOI: 10.2172/1755761
|View full text |Cite
|
Sign up to set email alerts
|

Complete Round-Robin Hydrogen Gas Analysis Capability Comparison (Milestone 2.6)

Abstract: The Department of Energy (DOE) is currently evaluating strategies for the extended dry storage of aluminum-clad spent nuclear fuel (ASNF). Part of this assessment concerns the extent of radiolytic molecular hydrogen (H 2 ) generation from the aluminum cladding's oxyhydroxide corrosion layers. Understanding this radiation-induced process and the factors affecting it (e.g., system conditions such as temperature and gaseous environment) are essential for the development of predictive computer models to support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Despite the variation in dose rate across the plate assembly surface, the As-Dried and As-Corroded assemblies feature the same dose rate profile, and so can be compared against each other. Furthermore, joint INL and SRNL experiments have demonstrated that the H2 G-value from similar aluminum radiolysis experiments is not strongly dependent on dose rate between 8 Gy/min and 175 Gy/min [8]. However, because it is yet unknown whether depletion of the water inventory may lead to an appreciable reduction in H2 generation rates in areas that experience very high total absorbed doses, caution should be used when comparing these radiolysis data to other experiments, as the reported H2 concentrations correspond to the total yield while the local yield might vary spatially across the assembly surface due to varying dose rate and levels of water depletion.…”
Section: Vessel Irradiationmentioning
confidence: 98%
“…Despite the variation in dose rate across the plate assembly surface, the As-Dried and As-Corroded assemblies feature the same dose rate profile, and so can be compared against each other. Furthermore, joint INL and SRNL experiments have demonstrated that the H2 G-value from similar aluminum radiolysis experiments is not strongly dependent on dose rate between 8 Gy/min and 175 Gy/min [8]. However, because it is yet unknown whether depletion of the water inventory may lead to an appreciable reduction in H2 generation rates in areas that experience very high total absorbed doses, caution should be used when comparing these radiolysis data to other experiments, as the reported H2 concentrations correspond to the total yield while the local yield might vary spatially across the assembly surface due to varying dose rate and levels of water depletion.…”
Section: Vessel Irradiationmentioning
confidence: 98%
“…To date, this program's irradiation studies have focused on the radiolytic formation of H2 from corroded surrogate aluminum alloy coupons, specifically 1100 and 6061, under a variety of conditions, including temperature, backfill gas composition, and relative humidity (RH) [16][17][18][19][20][21][22][23]. In these studies, corrosion was achieved by submerging the aluminum coupons in high purity water (18.2 MΩ•cm) at ~95 o C for 30 days, as benchmarked by Lister [24].…”
Section: Introductionmentioning
confidence: 99%
“…Although samples of the non-native corrosion plumes were not collected for characterization [29], given the temperature dependence of aluminum corrosion processes [30], the mineral phase composition of these plumes is expected to be different from the initial passivated corrosion layer and the hightemperature-corrosion layers investigated by our team [16][17][18][19][20][21][22][23]. Differences in layer composition will impact the extent of H2 production from these plumes, as demonstrated by the differences in H2 generation found for irradiated gibbsite and boehmite powders [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of H2 can lead to aluminum alloy embrittlement, canister pressurization, and the potential formation of explosive and/or flammable gas mixtures [5][6][7][8]. Consequently, the DOE Office of Environmental Management-Technology Development (EMTD) Technical Basis for Extended Dry Storage of Aluminum-Clad Spent Nuclear Fuel has spent several years investigating parameters-such as the extent of corrosion, absorbed gamma dose, gaseous environment (air, nitrogen, argon, and helium), relative humidity (RH), and temperature-that underpin the formation of H2 from irradiated surrogate cladding materials [9][10][11][12][13][14][15]. The data gathered by this initiative has been essential for the development of predictive computer models to support technical considerations and the identification of radiation related challenges for the extended dry storage of ASNF [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%